IMPLEMENTASI AJARAN TAMANSISWA â€œTRI NGAâ€ MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PEMBELAJARAN IPA KELAS IV SEKOLAH DASAR - Anik Dwi Nurmawati; Ana Fitrotun Nisa; Ahniasari Rosianawati; Budi Artopo; Riska Ashar Luthfia Erva; Nizhomi, Bestiana (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to implement the principles of Tamansiswa Tri Nga in science learning through the discovery learning model for the fourth grade of SD Baran I. Observation results show that during the current pandemic, teachers have difficulty designing learning activities that can encourage students to participate directly in real activities. This is because students learn from home. All learning activities at home cannot be monitored directly by the teacher. This research is descriptive qualitative research, which describes the implementation of Tri Nga principles through discovery learning models in online science learning for fourth-grade students of SDN Baran I. This research was conducted in SDN Baran I Rongkop, Gunungkidul in the online learning process for the fourth-grade science subjects in the 2021/2022 academic year. The subjects of this study were fourth-grade students of SDN Baran I Rongkop, with a total of 17 students, consisting of 11 male students and 6 female students. Data collection techniques used include observation techniques or observation and documentation rubrics. Through the discovery learning model in science learning by implementing Tri Nga's principles on online learning for the fourth grade of SDN Baran I can be carried out well. This is reflected in the implementation of learning to encourage students to be active and explore themselves. Students gain direct and meaningful experience regarding the material of plant and animal parts.